DETERMINANTS OF PARTICIPATION SURVIVORS COVID-19 AMONG â‰¥45 YEARS OLD TO COVID-19 THIRD DOSE VACCINATION: Determinan Partisipasi Penyintas COVID-19 Berusia â‰¥ 45 Tahun dalam Vaksinasi COVID-19 Dosis 3 - Wahidah, Putri Djamilah; Wardani, Hartati Eko; Alma, Lucky Radita; Gayatri, Rara Warih (Jurnal Berkala Epidemiologi, 2024)
Background: Booster vaccinations are a way to keep the body protected against COVID-19. Mojolangu Health Center is one of the densely populated areas which is part of the Lowokwaru sub-district and borders the Belimbing sub-district; the two sub-districts are ranked 2nd and 1st with the highest CFR (Case Fatality Rate) in Malang City. Therefore, examining public perceptions of vaccination to evaluate immunization programs and raise performance goals is essential. Purpose: To determine the relationship between the Health Belief Model components (perceived susceptibility, severity, benefits, barrier, and cues to action) and the participation of COVID-19 booster vaccination in survivors of COVID-19 aged â‰¥45 years. Conducted from April to November 2022, this research was located in the working area of Mojolangu Health Center (Mojolangu, Tunjungsekar, Tunggulwulung, and Tasikmadu village). Methods: This quantitative research used a case-control design study. This research sample comprised 82 people, selected using the purposive sampling technique with a 1:1 ratio for case and control. Data analysis was done using the Chi-Square test and Binary Logistics Regression tests. Results: The respondents were dominated by the middle age group (45-59 years), primarily entrepreneurs with a monthly income of more than IDR 3.5 million and domiciled in Mojolangu village. The perceived benefits variable showed p=0.04 (aOR=2.67; 95% CI=1.03-6.91) and perceived barriers p=0.01 (aOR=3.60; 95% CI=1.39-9.28), while perceived vulnerability p=1.00 (cOR=1.00; 95% CI= 0.32 – 3.16), perception of cues to act p= 0.18 (cOR= 1.82; 95% CI= 0.75 - 4.40). Conclusion: Factors related to booster vaccination participation are perceived benefits and barriers.